Przywództwo polityczne Władimira Putina - Kucharski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes the concept of political leadership and its specificity in the Russian Federation, using the figure of Vladimir Putin as a case study. Various leadership styles - democratic, authoritarian, and totalitarian are discussed, along with their application in the Russian political system. The evolution of the power model in Russia after 1991, the role of elites, and the mechanisms of Putin`s legitimization, particularly in the context of the Russian - Ukrainian War, are examined. The article highlights the authoritarian nature of Putin`s rule and his pursuit of restoring Russia`s power in the international arena.
Keywords: autorytaryzm; Federacja Rosyjska; przywództwo polityczne; Putin, Władimir Władimirowicz (1952- ); authoritarianism; Russian Federation; political leadership